PENGARUH LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN, DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN BARANG INDUSTRI KONSUMSI YANG TERDAFTAR DI BEI TAHUN 2014 – 2018 - Larosa Dayanara; Kartika Hendra Titisari; Anita Wijayanti (Universitas Slamet Riyadi, 2020)
This Research aims to test the leverage, profitability, size of the company and capital intensity against tax avoidance. On the research of these independent variables using Leverage, profitability of the company's size and capital intensity while the variable dependennya is tax avoidance. The population in this research is the company's industrial goods and consumption listed in Indonesia stock exchange period in 2014 - 2018 the company, using the method of purposive sampling yielded 13 companies that meet the criteria. This research uses linear regression analysis double. Results on the research indicates that the profitability of the company and the size effect on tax evasion while the variable doesn't effect on tax evasion. Based on the test results the coefficient of determination (R2) of earned 32.8% of tax avoidance variable can be explained by the variable leverage, profitability, size of the company and capital intensity, while the rest were 67.2% in the other factors explain by factors outside of the variables in the study.